Vascularization pattern of C6 glioma is modified with medroxyprogesterone acetate and ibuprofen in wistar rat brain - (:unkn) unknown (W.B. Saunders Ltd, 2001)
Beneficial effects of medroxyprogeslerone acetate (MPA) in cancer therapy is partly mediated via its antiangiogenic activity. The same is true for the antitumoral action of non-steroidal antiinflammatory drugs. We have studied two liposoluble drugs, MPA and the analgesic ibuprofen, on glioma vascularization in vivo. In this study we have shown that, until the sacrifice at 27. day after tumor inoculation in the right hemisphere, MPA had a slight though insignificant activity to reduce the fatality of C6 glioma, growing in right cerebral hemisphere of male Wistar rats. But ibuprofen both alone or with MPA had no effect on survival with gavage application of a 30 mg/kg/day dosing regime. On histological analysis, intra- and peritumoral vessels were counted. Progesterone seemed to lower intratumoral, but to increase peritumoral vessels, especially glomeruloids, around the tumor mass. Coadministration of ibuprofen acted to suppress the peritumoral vessel increase, and to enhance lymphomonocytic infiltration around tumor vessels. © 2001 W. B. Saunders & Company Ltd on behalf of the Arányi Lajos Foundation.
Keywords: Angiogenesis; Glioma; Ibaprofen; Medroxyprogesterone